Measuring the Influence of Self- Directed Learning on Argumentative Writing Outcomes: An Experiment Study - Jhon Sarip; Sabarun Sabarun (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The current study measured the effect of self- directed learning (SDL) on writing argumentative essay. One hundred twenty seven students were recruited as the participants of the investigation. The participants were classified to an experimental class (n =63) and a control class (n= 64) with cluster sampling technique. The experiment class were taught to implement SDL as a method for planning, designing, monitoring, and writing essays. The t test was employed to work with the data.Â  The analysis confirmed that there were significant differences (t (125) = 5.965, p = 0.000) in the scores with mean score for [Self-Directed learners] (M = 74.206, SD = 11.651) was higher than and [Non- Self Directed Learners] (M = 62.046, SD = 11.321). The mean differences (Md = 12.160, 95% CI: 8.125 to 16.194) was claimed to be significant.Â  It indicated that SDL gave positive significant effect on learners' argumentative writing skills. Participants who underwent SDL showed a significant improvement in their writing skills (p < 0.05).Â